Cognitive Behavior Pattern of Substance Use Among Individuals: Life Sciences - Sudish, R C; Ramachandran, Divya; Sanjeev Bansal, Prof. (Dr.) (International Journal of Life Science and Pharma Research, 2023)
Substance use is one of the intense topics in current times, especially due to the health and social effects impacted by its abuse. According to WHO, over 5% of the disease worldwide can be attributed to alcohol. Alcohol use has also significantly increased in the past decade among youth as they are more vulnerable to peer and societal pressure. Anti-substance use advertisements (e.g., media ads on television, print media, etc.) rely heavily on emotional reasoning to persuade people not to drink liquor. Still, its effectiveness is yet to be ascertained. Hence, this research aims to understand the cognitive behavior pattern of substance use among individuals. To achieve this aim, our objectives assessed were determining the factors that lead to avoidance of drinking liquor. These factors trigger liquor use among individuals and the role of the financial situation & living environment in the choice of liquor consumption. Alcohol was chosen as the substance for this study due to its popularity. Our investigation revealed that individuals stop liquor consumption mainly due to health problems, family issues, and negative effects. At the same time, stress and societal influence are the main reasons they consume liquor. Also, individuals staying with parents showed little or no tendency to drink liquor, while those staying with friends were prone to consume liquor occasionally. Therefore, the focus is shifting towards the systematic intervention of substance use during school life to reduce the burden of its consumption during adulthood and improvisation of anti-substance use advertisements that create fear arousals and are emotionally evocative.